Safety of 6-week Neonatal Triple-combination Antiretroviral Postexposure Prophylaxis in High-risk HIV-exposed Infants. Issue 10 (October 2019) - Anugulruengkitt, Suvaporn; Suntarattiwong, Piyarat; Ounchanum, Pradthana; Srirompotong, Ussanee; Jantarabenjakul, Watsamon; Sophonphan, Jiratchaya; Punnahitanon, Sunti; Pancharoen, Chitsanu; Cressey, Tim R.; Chokephaibulkit, Kulkanya; Puthanakit, Thanyawee
Abstract : Background: Combination antiretroviral drug regimens are increasingly preferred for neonatal postexposure prophylaxis (PEP) among HIV-exposed infants with high-risk of transmission. We evaluated the adverse events associated with the use of zidovudine (ZDV)/lamivudine (3TC)/nevirapine (NVP) for neonatal PEP during the first 6 weeks of life. Methods: A prospective cohort of non-breast-fed HIV-exposed infants was conducted at 5 clinical sites in Thailand. Study population included 100 high-risk HIV-exposed infants (maternal HIV RNA > 50 copies/mL prior to delivery or received antiretroviral therapy less than 12 weeks) and 100 low-risk HIV-exposed neonates. High-risk infants received ZDV/3TC/NVP for 6 weeks whereas low-risk HIV-exposed neonates received a 4-week regimen of ZDV. Complete blood count, aspartate transaminase and alanine transaminase were assessed at birth, 1, 2 and 4 months of life. Results: From October 2015 to November 2017, 200 infants were enrolled, of which 18.5% had low birth weight < 2500 g. The proportion of infants with anemia grade 2 or higher at 1 and 2 months of life between ZDV/3TC/NVP and ZDV prophylaxis was 48.5% vs 32.3% ( P =0.02); nevertheless, severe anemia (grade 3) was not significantly different; 9.2% vs 10.2% ( P =0.81), respectively. At 1 month old, infants on ZDV/3TC/NVP prophylaxis had significantly higher grade 2 anemia versus infants on ZDV alone (33.0% vs 13.4%; P =0.001); however, no difference was observed at 2 months old. No differences in neutropenia or hepatotoxicity between infant prophylactic regimens were observed. Conclusions: Triple antiretroviral neonatal PEP with ZDV/3TC/NVP for 6 weeks in high-risk HIV-exposed infants did not significantly increase the risk of short-term toxicity compared with ZDV-monotherapy prophylaxis.